ZnSnN2 in Real Space and k‐Space: Lattice Constants, Dislocation Density, and Optical Band Gap. Issue 16 (18th May 2021) - Olsen, Vegard Skiftestad; Øversjøen, Vetle; Gogova, Daniela; Pécz, Béla; Galeckas, Augustinas; Borgersen, Jon; Karlsen, Kjetil; Vines, Lasse; Kuznetsov, Andrej
Abstract: Semiconducting II‐IV nitrides exhibit tunability of optoelectronic properties similar to that of the group III nitrides, while comprising earth‐abundant and potentially low‐cost elements. However, the II‐IV nitrides synthesis is immature, limiting the explorations. Herein, ZnSnN2 hetero‐epitaxial films grown by high‐power impulse magnetron sputtering, having the quality at the level of the III‐nitrides layers grown without dislocation‐reducing strategies are demonstrated. This breakthrough, in addition to paving the way toward potential applications, enables reliable measurements of the ZnSnN2 properties in real space and k ‐space. In particular, for wurtzite ZnSnN2 films with total dislocation density of ≤ 5 × 10 10 cm −2, the lattice parameters and the optical band gap ( E g ) are determined with the accuracy not being accessible before for this material, e.g. E g  = 1.67 ± 0.03 eV. Thus, looking retrospectively, the authors' data set the ZnSnN2 —and perhaps more generally the II‐IV nitrides—at the stage comparable to that of the beginning of the III‐nitrides rising era. Abstract : Wurtzite ZnSnN2 hetero‐epitaxial films are demonstrated having the quality at the level of the III‐nitrides layers grown without dislocation‐reducing strategies. This breakthrough, in addition to paving the way toward potential applications with an earth‐abundant material, enables reliable measurements of the hexagonal ZnSnN2 properties in real space and k ‐space.